Aviva's piano - Chaikin, Miriam (New York Clarion Books, 1986)
Aviva's piano is too large to fit through the door of her home on the kibbutz, until a terrorist's bomb provides an unexpected solution.
Keywords: Collective settlements -- Israel -- Juvenile fiction; Israel -- Juvenile fiction; Kibbutzim -- Fiction; Piano -- Fiction